Sleeping Beauties. - Geeraerts, Ann; Vanackere, Luc; Kasteel van Gaasbeek, Lennik (Oostkamp : Stichting Kunstboek, 2011)
Viola, Bill ; Tunick, Spencer ; Serrano, Andres ; Schacht, Kelly ; Schalken, Tobias ; Op de Beeck, Thomas ; Martin, Kris ; Fabre, Jan ; Dujourie, Lili ; Claerbout, David ; et al.
Sleeping Beauties, Kasteel van Gaasbeek, Lennik, 9.09 - 13.11.2011
kunstcatalogus